The Independent Learners’ Effort and Their Oral Communication Achievement During Pandemic - Intan Soraya; Ali Mustofa; Him’mawan Adi Nugroho (LP. Ma'arif Janggan Magetan, 2024)
During the pandemic Covid 19, the situation of teaching and learning English was different from yesterday. with limiting time in the process of study, make the teacher and also the students don’t have much time to communicate directly. They have space for communication. caused the class setting to be online. it makes the students have to be creative in learning. Utilizing the media is needed. Therefore, the students use to be independent in learning The research purpose was to (1) explain the independent learners’ effort to acquire English as Foreign Language and (2) find out independent learners’ oral communication skill achievement from their efforts. This research method is qualitative descriptive. Triangulation is used to make sure the data has been valid. The collecting of data is observation based on the fact that happen before the pandemic and during the pandemic, informant interviews, and document analysis. The technique of validity data used triangulation. The technique of data analysis uses Miles and Huberman’s interactive model. The result of this research shows that independent learners have been creative in the learning process. followed by the score to prove the research has been done in the field of the target.